2012
DOI: 10.1371/journal.pone.0036238
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and Comparative Gene Expression Analysis of Sogatella furcifera (Horváth) in Response to Southern Rice Black-Streaked Dwarf Virus

Abstract: BackgroundThe white backed planthopper (WBPH), Sogatella furcifera (Horváth), causes great damage to many crops by direct feeding or transmitting plant viruses. Southern rice black-streaked dwarf virus (SRBSDV), transmitted by WBPH, has become a great threat to rice production in East Asia.Methodology/Principal FindingsBy de novo transcriptome assembling and massive parallel pyrosequencing, we constructed two transcriptomes of WBPH and profiled the alternation of gene expression in response to SRBSDV infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
82
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 64 publications
12
82
1
3
Order By: Relevance
“…Of the SSRs, 21.09, 31.71, and 42.53% were mononucleotide, dinucleotide, and trinucleotide repeats, respectively (Figure 3). The results demonstrated that trinucleotide repeats were the most abundant microsatellites in this transcriptome data set, which is consistent with other recent reports in insects (Xu et al, 2012). Among all of the SSR types, AAC/GTT (21.58%) represented the dominant type, followed by A/T (21.02%), AG/CT (14.29%), AT/AT (8.53%), and AC/GT (8.32%) ( Table S4).…”
Section: Ssr Discoverysupporting
confidence: 93%
“…Of the SSRs, 21.09, 31.71, and 42.53% were mononucleotide, dinucleotide, and trinucleotide repeats, respectively (Figure 3). The results demonstrated that trinucleotide repeats were the most abundant microsatellites in this transcriptome data set, which is consistent with other recent reports in insects (Xu et al, 2012). Among all of the SSR types, AAC/GTT (21.58%) represented the dominant type, followed by A/T (21.02%), AG/CT (14.29%), AT/AT (8.53%), and AC/GT (8.32%) ( Table S4).…”
Section: Ssr Discoverysupporting
confidence: 93%
“…The key components of the RNAi pathway are highly conserved within insect species (12). To obtain the sequences encoding the core components of the RNAi pathway in the transcriptome of SBPH or WBPH, we used a local BLASTN search with sequences of Nilaparvata lugens (JX023532.1, JX644040.1, KC316038.1, and JX644040.1 for DCR2, DCR1, AGO2, and AGO1, respectively) as queries (18,20,34). The SBPH DCR2 and AGO2 and WBPH AGO2 gene sequences were obtained from the GenBank (accession numbers JX023531.1, JX023533.1, and JX023535.1, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…The plant reoviruses, plant rhabdoviruses, tospoviruses, and tenuiviruses are transmitted in a persistent propagative manner by sap-sucking insect vectors, including thrips, aphids, planthoppers, and leafhoppers (1)(2)(3). The key siRNA pathway factors DCR2 and AGO2 are conserved in sap-sucking insects that transmit persistent propagative plant viruses (15)(16)(17)(18)(19)(20). Indeed, the RNAi pathway is triggered by the replication of persistent propagative plant viruses in insect vectors (15)(16)(17)(18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, viruses have evolved a large number of strategies to modulate the UPS process. Virus infection can affect the transcription levels of genes important for the UPS process (35,36). Alternatively, viruses also can modulate the UPS process by directly interacting with UPS components.…”
mentioning
confidence: 99%